Wakil Gubernur dan Keistimewaan DIY - Bambang Purwoko; Wawan Mas'udi (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2001)
The status of Yogyakarta as a special province has brought about a serious tension at both conceptual as well as practical levels. A close look at the process around the recruitment of the Vice Governor for this province shows that point. A new interpretation and design of Yogyakarta as a special province is demanded.